Case: Autonomous R2R systems : autosys - Määttä, Harri (An active attitude and the spirit of doing : hands-on work and results at the Information Technology department of Oulu UAS, 2014)
The objective of Autonomous R2R (Roll-to-Roll) systems is to extend the capabilities of R2R manufacturing from single component manufacturing and integration of functional systems to the pilot production level. Running the pilot lines continuously, the PrintoCent community and companies learn about the capabilities, bottle necks and design guidelines of a real production environment.
Keywords: tulostettava elektroniikka; tryckt elektronik